2022
DOI: 10.1007/s10570-022-04737-w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydroxyethyl and carboxymethyl celluloses on the rheology, water retention and surface tension of water-suspended microfibrillated cellulose

Abstract: Water-soluble polymers have been shown to improve the flow rigidity and water retention ability of highly-branched (flocculated) and polydisperse water-suspended MFC, thereby also modifying and controlling their rheological behaviour. The addition of hydroxyethyl (HEC) and carboxymethyl (CMC) celluloses of different content (5–10–20 w/w%), molecular weights (MW, 90.000–1.300.000 g/mol) and degrees of substitutions (DS, 0.7–1.2) to 1.5 wt% MFC suspension, have thus been studied by evaluating their microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The ζ-potential value of this alkali-based modified polymer was −52.4 mV, indicating good stability of particles in aqueous solution. The increased ζ-potential value was due to the complete dissociation of NaOH in the solution . The addition of the alkali increases the concentration of OH – ions and raises the pH, leading to an increased quantity of hydroxyl groups on the surface of cellulose particles, consequently enhancing the surface charge repulsion and increasing the particle stability by reducing fluctuation.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ζ-potential value of this alkali-based modified polymer was −52.4 mV, indicating good stability of particles in aqueous solution. The increased ζ-potential value was due to the complete dissociation of NaOH in the solution . The addition of the alkali increases the concentration of OH – ions and raises the pH, leading to an increased quantity of hydroxyl groups on the surface of cellulose particles, consequently enhancing the surface charge repulsion and increasing the particle stability by reducing fluctuation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The change in viscoelastic behavior indicated that at higher concentrations, the polymer cross-linking network in terms of hydrogen bonding or entanglement of polymer chains was not permanent and rearranged its molecular structure in response to the frequency. , The characterization of rheological properties of polysaccharide solutions in oscillatory shear usually focuses in the linear viscoelastic (LVE) region where the applied strain amplitude is sufficiently small . The behavior of the cellulose ethers and their derivatives is affected by the change in frequency in the linear viscoelastic region under constant low stress, where the rheological behavior is independent of the shear strain and only depends on the microstructure and temperature. , By increasing concentration from 0.50 to 1 wt %, the elastic modulus becomes dominant, which shows the gel-like behavior of modified DEC-HEMC solution. The cellulose ethers and other polymers exhibited a similar pattern due to the interlocking of polymer coils. , The point of intersection in the transition corresponds to the flow point [ G ′ = G ′′] that becomes more complex with increasing concentration due to higher density of the solutions. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It presents strong in uences of concentration (Pääkko et al 2007;Rezayati Charani et al 2013) and pH (Pääkko et al 2007). Furthermore, the rheology of suspensions can be modulated with the use of salts (Costa, Costa, and Simões 2019), organic solvents (Costa et al 2019; Da Silva et al 2018), cellulose derivatives (Kokol 2022) and carbohydrates (Lameirinhas et al 2023;Sorvari et al 2014). In the case of cellulose derivatives, as they share the same main structure as cellulose, it is possible that the adsorption of cellulose derivatives on MFC will involve the alignment of the chains of both polymers (Hubbe et al 2017).…”
Section: Introductionmentioning
confidence: 99%